2009
DOI: 10.4161/cbt.8.9.8129
|View full text |Cite
|
Sign up to set email alerts
|

Comparitive study of efficacy, tolerability of four field box technique vs. two field anterior posterior technique in locally advanced carcinoma cervix:A prospective analysis

Abstract: Both two and four field box techniques are equally effective and feasible as statistically insignificant difference in the response rate and acute toxicities was observed in the two arms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…For a portion of patients, there could a chance to utilize radiation treatment instead of surgery, pointing organ assurance (Adegoke, Kulasingam, & Virnig, 2012;Barton & Delaney, 2010). To treat the cervix cancer, a customary procedure of box strategy or high energy photon (2-dimensional) with AP/PA fields have been reported (Gupta et al, 2009). It has been observed that the use of customary method delivered superfluous dosages to adjacent basic organs, subsequently driving to treatment related complications which were an enormous issue, especially considering the high rate of remedy versus survival of illness.…”
Section: Introductionmentioning
confidence: 99%
“…For a portion of patients, there could a chance to utilize radiation treatment instead of surgery, pointing organ assurance (Adegoke, Kulasingam, & Virnig, 2012;Barton & Delaney, 2010). To treat the cervix cancer, a customary procedure of box strategy or high energy photon (2-dimensional) with AP/PA fields have been reported (Gupta et al, 2009). It has been observed that the use of customary method delivered superfluous dosages to adjacent basic organs, subsequently driving to treatment related complications which were an enormous issue, especially considering the high rate of remedy versus survival of illness.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, a conventional technique using high photon energy with AP/PA fields or box technique was used for treatment of carcinoma of the cervix. 2 It was observed that the conventional technique delivered unnecessary doses to nearby critical organs, thereby leading to treatment related complications which was a big issue considering the high rate of cure and survival of disease. This was a problem we had to accept to cure the disease (Figs.…”
Section: Introductionmentioning
confidence: 99%